Jak diagnostikovat sarkoidózu srdce? - Doubková, Martina; Panovský, Roman (Vnitrni lekarstvi, 2018)
Sarcoidosis is a systemic granulomatous disease of unknown etiology that can affect any organ including the heart. Clinical manifestations of heart disease are seen in about 5 % of patients, but histology shows a higher rate of heart involvement by sarcoidosis. Therefore, heart sarcoidosis is underdiagnosed because of clinically non-symptomatic course in some patients or physicians simply do not think about this heart involvement. Echocardiography, Holter monitoring, magnetic resonance imaging, positron emission tomography/computed tomography, thallium scintigraphy, and endomyocardial biopsy are methods of investigation when suspected of heart involvement by sarcoidosis. In particular, magnetic resonance has gained importance recently in the diagnosis of cardiac sarcoidosis. Key words: cardiac sarcoidosis - diagnostics - therapy.
Keywords: biopsie; sarkoidóza; Cardiomyopathies; Biopsy; Sarcoidosis; Humans; lidé; Positron Emission Tomography Computed Tomography; PET/CT; kardiomyopatie